2010
DOI: 10.1179/174328109x463039
|View full text |Cite
|
Sign up to set email alerts
|

Effects of slag composition and cooling rate on formation of glaze on MgO refractory

Abstract: The formation of a slag glaze layer on dense and porous MgO rods was studied by dipping MgO rods into liquid slag at 1873 K and thereafter cooling the rods at a predetermined cooling rate. Three different slag compositions and three different cooling rates were employed. It was found that the phases formed upon cooling were mostly dependent on slag composition and to a minor extent on the cooling rate. The initially liquid slag was transformed into crystalline phases for all the samples except the ones termina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 12 publications
(28 reference statements)
1
5
0
Order By: Relevance
“…In recent studies, 15,16 the solidification of ladle glaze and the precipitation of solid particles in the ladle slag system were investigated. Four phases were mainly detected in the glazed refractory, which was in contact with the slag.…”
Section: Solidification Of Adhered Ladle Slagmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent studies, 15,16 the solidification of ladle glaze and the precipitation of solid particles in the ladle slag system were investigated. Four phases were mainly detected in the glazed refractory, which was in contact with the slag.…”
Section: Solidification Of Adhered Ladle Slagmentioning
confidence: 99%
“…In the next heat, more non-metallic inclusions could be generated from the accumulated slag being washed out from the ladle pores. In fact, based on their experimental study, 16 the authors have shown the formation of cracks, and dusted slag occurs with high SiO 2 content slag, i.e. 12 or 15 mass-%SiO 2 .…”
Section: Solidification Of Adhered Ladle Slagmentioning
confidence: 99%
“…Doostmohammadi et al 2 have compared two and three dimensional methods for inclusion determinations. Song and co-workers [3][4][5][6] have studied the influence of ladle glaze on the inclusion characteristics. Bjo ¨rklund et al 7 have studied the effect of ladle treatment on the inclusion composition.…”
Section: Introductionmentioning
confidence: 99%
“…All slag compositions were successfully foaming, but unfortunately, slag 1 and slag 5 pulverised almost spontaneously after solidification, probably due to their high CaO/SiO 2 ratio which led to dusting of the slag [25]. Only the heights of these foams could be measured, while attempts to collect other information were not successful.…”
Section: Resultsmentioning
confidence: 99%
“…A concept of foaming index was introduced [8] to describe the foaming height using the retention time of gas passing through the slag. Although the foaming index has been used widely in the steel industry, researchers have also found that some slags deviate from the index equation [22,25]. Millman et al studied the refining process in an experimental converter, and at the same time slag foaming.…”
Section: Introductionmentioning
confidence: 99%